2017
DOI: 10.18632/oncotarget.22184
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA co-expression networks exhibit increased complexity in pancreatic ductal compared to Vater's papilla adenocarcinoma

Abstract: MiRNA expression abnormalities in adenocarcinoma arising from pancreatic ductal system (PDAC) and Vater's papilla (PVAC) could be associated with distinctive pathologic features and clinical cancer behaviours. Our previous miRNA expression profiling data on PDAC (n=9) and PVAC (n=4) were revaluated to define differences/similarities in miRNA expression patterns. Afterwards, in order to uncover target genes and core signalling pathways regulated by specific miRNAs in these two tumour entities, miRNA interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…Interestingly, miR-323a-3p was also reported as over-expressed in pancreatic ampullary tumors and found to participate in interaction networks, modulating gene expression including KRAS , with roles in axon guidance pathway [60]. Results from this and our study suggest alternative miRNA regulatory networks modulating similar pathways in AMP cancers.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, miR-323a-3p was also reported as over-expressed in pancreatic ampullary tumors and found to participate in interaction networks, modulating gene expression including KRAS , with roles in axon guidance pathway [60]. Results from this and our study suggest alternative miRNA regulatory networks modulating similar pathways in AMP cancers.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies compared global miRNA expression profiles in PDAC and AMP and showed that miRNA expression profiles are distinct between PDAC and AMP tumors [1620].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these proteins have been confirmed to play key roles in cancer pathogenesis [7, 19]. Although some studies have revealed that many circRNAs act as regulators in the development of PDAC [20, 21], the actual circRNAs involved and their functions remain unclear. According to previous studies, noncoding RNAs regulate gene expression via two main ways: cis-acting and transacting regulation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-339-3p was found to be deregulated in Vater’s papilla adenocarcinoma [ 38 ]. In addition, miR-339-3p was downregulated in colorectal cancer (CRC) and its low-level expression was associated with lymph node metastasis in patients with CRC [ 39 ].…”
Section: Resultsmentioning
confidence: 99%